2020
DOI: 10.3390/molecules25215066
|View full text |Cite
|
Sign up to set email alerts
|

Two-Photon Polymerized Poly(2-Ethyl-2-Oxazoline) Hydrogel 3D Microstructures with Tunable Mechanical Properties for Tissue Engineering

Abstract: The main task of tissue engineering (TE) is to reproduce, replicate, and mimic all kinds of tissues in the human body. Nowadays, it has been proven useful in TE to mimic the natural extracellular matrix (ECM) by an artificial ECM (scaffold) based on synthetic or natural biomaterials to regenerate the physiological tissue/organ architecture and function. Hydrogels have gained interest in the TE community because of their ability to absorb water similar to physiological tissues, thus mechanically simulating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…BA740 also was used in the fabrication of a newly introduced macromonomer based on poly(2‐oxazoline)s PEtOx‐DA for 2PP. In combination with the photo initiator BA740 and the new macromonomer several investigations were performed and showed that highly precise 3D‐microstructures in from of spiderwebs could be fabricated [8,63] …”
Section: D‐π‐a‐π‐d Chromophoresmentioning
confidence: 99%
See 1 more Smart Citation
“…BA740 also was used in the fabrication of a newly introduced macromonomer based on poly(2‐oxazoline)s PEtOx‐DA for 2PP. In combination with the photo initiator BA740 and the new macromonomer several investigations were performed and showed that highly precise 3D‐microstructures in from of spiderwebs could be fabricated [8,63] …”
Section: D‐π‐a‐π‐d Chromophoresmentioning
confidence: 99%
“…In combination with the photo initiator BA740 and the new macromonomer several investigations were performed and showed that highly precise 3D-microstructures in from of spiderwebs could be fabricated. [8,63] Huang et al took advantage of the easy chemical modifiability of the terminal amino residues, similar to BA740. The authors equipped the photo initiator PBDA with acryloyl groups, aiming to bind it to the produced gel during polymerization and thus limit its release or mobility.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…Polyoxazolines are polymers with particularly interesting properties; thanks to their structural versatility, many reviews reported the possibilities offered by these polymers when it comes to the ease of the synthesis methods [60], the control of the macromolecular architectures and design of the copolymers [61], the modulation of the hydrophilicity of the polymer chains [62], making self-assemblies and hydrogels [63,64], and biocompatibility and applicability in the biomedical domains [65]. These polymers are now usually synthesized by cationic ring-opening polymerization of oxazolines; a polymerization reaction that has greatly 9 Advances in Polymer Technology benefited from the emergence of MW heating in the polymer chemistry notes that the synthesis of polyoxazolines by conventional heating suffered for a long time from low kinetics before multiplying its rate by 400 thanks to MWs.…”
Section: Advances In Polymer Technologymentioning
confidence: 99%
“…Following the programmable shape morphing, we display and identify several reconfigurable micro-scale structures by applying external stimuli for the first time. Shown by the cell loading experiment (Figures 1c, S1 and S2), the hydrogels allow fibril cells to crawl on the surface freely after one week, and the summarized cell viability exceeds 98%, implying the as-prepared hydrogels to be ready for cell culture [6,38] or tissue engineering. Interestingly, the optical double-frequency technique is adopted here for generating the 532 nm green femtosecond laser beam during TPP fabrication for the first time.…”
Section: Introductionmentioning
confidence: 99%